La ética y sus desafíos en la gestión empresarial: comportamientos y prácticas en la gestión diaria - Guerra Garib, Renato Pedro (2025)
The paper examined how organizations approach and apply ethics in the business environment based on a review of previous research, with the aim of analyzing ethics in companies and their ethical challenges, evaluating the behavior of such organizations in their daily management. Topics such as ethical challenges and corruption, social responsibility and organizational behavior, ethical practices and strategies, leadership and ethical behavior, as well as research on business ethics were explored in depth. The study corresponds to a literature review under the criteria of descriptive research. The documentary analysis technique was used; therefore, 30 papers indexed in Scopus and hosted in Scimago Journal were analyzed, highlighting the importance of establishing a solid ethical framework in companies to promote responsible practices and mitigate risks associated with unethical behavior. The results show that companies with a well-defined ethical culture tend to generate greater trust among their employees, customers, and society in general. The review shows that, although the literature on business ethics is extensive, there are still areas that require further research, such as the impacts of ethics on financial performance and the effectiveness of ethical policies in multicultural contexts. In conclusion, the paper provides an overview of ethical practices and highlights the relevance of ethics in the sustainability and reputation of companies in a globalized and increasingly competitive environment.